Harmonic load-flow approach based on the possibility theory - Romero Quete, Andrés Arturo (2011)
Harmonics in power systems are responsible for several technical problems that justify the development of models to study them. Well-established models exist to analyse the harmonic load-flow (HLF) from a deterministic point of view. Moreover, models based on the probability theory have been developed to deal with the inherent variability and random nature of loads, network configuration etc. In the last few years, possibility theory has arisen as an alternative tool that in many cases could be better suited to describe and quantify the real nature of the uncertainty involved in harmonic studies. In this study a methodology for HLF calculation based on the possibility theory is presented. Possibility distributions instead of probabilities are the input used to describe the uncertainty in the magnitude and composition of the loads. Tests presented shows that the results of the proposed model are consistent with those obtained with a probabilistic method, and that both models lead to the same ranking of the risk that the bus harmonic voltages exceed a given level. Independent possibility distributions are assumed at the development stage reported here; research is being carried out in order to overcome this constraint.